The political interests of gender revisited : redoing theory and research with a feminist face - Anna G. Jónasdóttir; Jones, Kathleen B., 1949- (Tokyo ; New York : United Nations University Press, 2009)
This collection of theoretical and empirical research on gender and politics assembles contributions from a group of international scholars providing varied accounts of the political interests of gender. It examines how to bridge the gap between discursive and socio-materialist accounts of gender relations and politics. Offering new models for theoretical and empirical research, the first five chapters provide a theoretical framework for the collection, while the following eight chapters shed light on key concepts through detailed case studies of such topics as human rights, womens movements, gendered labor markets, international monetary policy, equality policy, and queer politics.--Publisher's description.
The political interests of gender revisited : reconstructing feminist theory and political research / Anna G. Jónasdóttir and Kathleen B. Jones -- Out of epistemology : feminist theory in the 1980s and beyond / Anna G. Jónasdóttir and Kathleen B. Jones -- Feminist questions, Marx's method and the theorisation of "love power" / Anna G. Jónasdóttir -- Empowerment, development and women's liberation / Ann Ferguson -- To teach "the correct procedure for love" : matrilineal cultures and the nation state / Maria-Barbara Watson-Franke -- Confronting power and politics : a feminist theorising of gender in Commonwealth Caribbean societies / Eudine Barriteau -- Men, power and the problem of gender equality policy implementation / Ingrid Pincus -- Explanations of internal sex segregation in a male dominated profession : the police force / Berit Åberg -- Queer citizenship/queer representation : politics out of bounds? / Kathleen B. Jones and Sue Dunlap -- Injecting a woman's voice : conservative women's organisations, gender consciousness and the expression of women's policy preferences / Ronnee Schreiber -- Women in movement : transformations in African political landscapes / Aili Mari Tripp -- European Central Bank, monetary policy and the "social europe" / Brigitte Young -- Private pain/public peace : women's rights as human rights and Amnesty International's report on violence against women / Gillian Youngs.
Includes bibliographical references and index.
Keywords: Feminist theory; Political science